2020
DOI: 10.1186/s12905-020-0890-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual contraception method utilization and associated factors among sexually active women on antiretroviral therapy in Gondar City, northwest, Ethiopia: a cross sectional study

Abstract: Background: Mother to child transmission is responsible for 90% of child infection with human immune deficiency virus (HIV). Dual contraceptive use is one of the best actions to prevent mother's human immune deficiency virus transmission to her child and partner. This study aimed at assessing the prevalence and factors associated with dual contraceptive use among sexually active women on antiretroviral therapy in Gondar City, northwest, Ethiopia. Methods: An institution based cross sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 30 publications
3
25
0
1
Order By: Relevance
“…The evidence is supported by a study done in Gondar, Ethiopia. 22 This can be explained by urban resident women being more exposed to health information and media outlets. This empowers them to have informed decision-making power and an easy discussion with their partners about contraceptive methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence is supported by a study done in Gondar, Ethiopia. 22 This can be explained by urban resident women being more exposed to health information and media outlets. This empowers them to have informed decision-making power and an easy discussion with their partners about contraceptive methods.…”
Section: Discussionmentioning
confidence: 99%
“…Women aged 15-24 years, urban residence, disclosing HIV status to a partner, marital status, higher educational level, employed women, discussion with contraceptive provider, received HIV counseling, and having a higher CD4 cell count were more likely to utilize dual contraceptive methods. 9,[15][16][17][18][20][21][22][23][24] Currently, in Ethiopia, HIV transmission is still high and many HIV positive reproductive age group women are still facing unintended pregnancy. 8 This directly related to risk of pregnancy-related complications, mother-to-child transmission of HIV, and transmission of HIV to their sexual partners due to low dual contraceptive utilization.…”
Section: Introductionmentioning
confidence: 99%
“… 14 To avoid unintended pregnancy and vertical transmission of HIV from mothers to child dual contraceptive utilization was taken as the better strategy. 15 …”
Section: Introductionmentioning
confidence: 99%
“…5 Different studies done in Ethiopia indicated that the utilization of dual method contraception was found to be low. 15 , 18 , 19 This is quite unexpected in a country where contraceptive services are virtually for free. The Ethiopian Demographic and Health Survey of 2016 revealed that 8% of pregnancy in Ethiopia was not wanted, and also 17% of pregnancy was mistimed.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia context different primary studies were conducted to estimate the prevalence of dual contraceptive utilization among HIV positive women [ 13 – 30 ] (Tewabe T, Abdanur A, Jenbere D, Ayehu M, Talema G: Contraceptive use and associated factors among sexually active HIV positive women attending ART clinic in FHRH in Bahir Dar, north west, Ethiopia. Facility based cross-sectional study.…”
Section: Introductionmentioning
confidence: 99%